Bleeding data: The case of fertility and menstruation tracking apps - Anastasia Siapka; Elisabetta Biasin (Internet Policy Review, 2021)
Journalists, non-profits and consumer organisations, as well as the authors' first-hand review of relevant privacy policies reveal that fertility and menstruation tracking apps (FMTs) collect and share an excessive array of data. Through doctrinal legal research, we evaluate this data processing in light of data and consumer protection law but find the commonly invoked concepts of "vulnerability", "consent" and "transparency" insufficient to alleviate power imbalances. Instead, drawing on a feminist understanding of work and the autonomist "social factory", we argue that users perform unpaid, even gendered, consumer labour in the digital realm and explore the potential of a demand for wages.
Keywords: 300; Data privacy; Fertility tracking; Consumer protection; Mobile apps